Neoadjuvant Therapy Using Checkpoint Inhibitors before Radical Cystectomy for Muscle Invasive Bladder Cancer: A Systematic Review - Hadi SHSM (MDPI AG, 2021)
Background: Neoadjuvant chemotherapy is the standard of care before radical cystectomy for muscle invasive bladder cancer. Recently, checkpoint inhibitors have been investigated as a neoadjuvant treatment after the reported efficacy of checkpoint inhibitors in metastatic urothelial carcinoma. Objectives: The aim of this systematic review is to investigate the role of checkpoint inhibitors as a neoadjuvant treatment for muscle invasive bladder cancer before radical cystectomy. Methods: Based on the PRISMA statement, a systematic review of the literature was conducted through online databases and the American Society of Clinical Oncology (ASCO) Meeting Library. Suitable publications were subjected to full-text assessment. The primary outcome of this review was to identify the impact of neoadjuvant immunotherapy on the oncological outcomes and survival benefits. Results: From the retrieved 254 results, 8 studies including 404 patients were included. Complete response varied between 30% and 50%. Downstaging varied between 50% and 74%. ≥Grade 3 AEs were recorded in 8.6% of patients who received monotherapy with either Atezolizumab or Pembrolizumab. In patients who received combination treatment, the incidence of ≥Grade 3 AEs was 16.3% for chemoimmunotherapy and 36.5% for combined immunotherapy. A total of 373 patients (92%) underwent radical cystectomy. ≥Grade 3 Clavien-Dindo surgical complications were reported in 21.7% of the patients. One-year overall survival (OS) and relapse-free survival (RFS) varied between 81% and 92%, and 70% and 88%, respectively. Conclusion: The evidence on the use of immune checkpoint inhibitors in the setting of pre-radical cystectomy is quite limited, with noted variability within published trials. Combination with chemotherapy or another checkpoint inhibitor may boost response, although prospective studies with extended follow-up are needed to report on the survival advantages.